Data-Driven Decisions: Leveraging Analytics for Strategic Marketing Management - Tanjung, Febrina Soraya (Equator Journal of Management and Entrepreneurship (EJME), 2024)
This study investigates the impact of data-driven decision-making, customer data utilization, and predictive analytics on the marketing performance of small and medium enterprises (SMEs) in Medan. Utilizing a quantitative research design, data was collected through structured questionnaires from a sample of 83 SMEs that possess a Business Identification Number (NIB). The analysis involved statistical techniques, including t-tests, F-tests, and regression analysis, using the Statistical Package for the Social Sciences (SPSS). The results reveal a significant positive relationship between the independent variables and marketing performance, with the regression model explaining approximately 58.3% of the variance in marketing outcomes. Findings indicate that prioritizing data-driven strategies can lead to enhanced decision-making and improved business performance for SMEs. This research contributes valuable insights for practitioners and scholars by highlighting the critical role of analytics in developing effective marketing strategies and fostering sustainable growth in a competitive landscape.